The calculus simulation to predict reliably heat transfer coefficient - Kang Dai; Lu Qin; Yanliu Guo; Yunjing Liang; Yannan Yang; Dan Zhao; Xincai Xiao (Case Studies in Thermal Engineering)
Strengthening heat transfer for energy conservation challenges current longer times and higher experimental costs on laboratory scale test, pilot scale test, industrialized production. It is critical to develop an effective and efficient method to simulate process of the heat transfer. Here, a calculus method to predict heat transfer coefficient was reported for the first time. The straight tube heat transfer equipment is the classic and the most studied type. The corrugated tube is like straight tube, consists of short straight section and corrugated section, which can strengthen effect of the heat transfer because of changing fluid field resulting from the corrugated section. According to the calculus principle, a single corrugated tube was chosen as researched object to rule out the effects of fluid inter-disturbance devised from multi-tubes. And a microunit of the corrugated tube acted as a short straight tube unit and computed micro-heat-transfer-coefficient, finally a integral heat transfer coefficient was obtained. The results demonstrate that the integral heat transfer coefficient was generally greater than the traditional value obtained under the equivalent diameter method while in recognition of the engineering error range. Collectively, the effectiveness demonstrates the potentiality of the calculus method on obtaining the integral heat transfer coefficient and designing shape function of heat transfer tubes.